2012
DOI: 10.1002/dta.1417
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS and GC‐IRD studies on the six‐ring regioisomeric dimethoxybenzylpiperazines (DMBPs)

Abstract: Gas chromatography with infrared detection (GC-IRD) provides direct confirmatory data for the differentiation between the six regioisomeric aromatic ring substituted dimethoxybenzylpiperazines (DMBPs). These regioisomeric substances are resolved by GC and the vapour-phase infrared spectra clearly differentiate among the six dimethoxybenzyl substitution patterns. The mass spectra for these regioisomeric substances are almost identical. With only the 2,3-dimethoxy isomer showing one unique major fragment ion at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The mass spectrum in Fig. provides support that the fragmentation pathway for these N ‐methylpiperazines in this study is equivalent to the previously reported monosubstituted dimethoxybenzylpiperazines . The mass spectrum in Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The mass spectrum in Fig. provides support that the fragmentation pathway for these N ‐methylpiperazines in this study is equivalent to the previously reported monosubstituted dimethoxybenzylpiperazines . The mass spectrum in Fig.…”
Section: Resultssupporting
confidence: 87%
“…This ion is a characteristic fragment for the piperazine ring and is almost universal in all N ‐1‐monosubstituted piperazines (N‐4 substituent is hydrogen). This m/z 56 ion yielded a mass shift of +6 Da when d 8 ‐piperazine was used to label all the four carbons of the piperazine ring . Thus, the m/z 56 ion was confirmed to contain six hydrogen atoms and three of the carbons from the original piperazine portion of these molecules; this confirmation was based on studies in the dimethoxybenzylpiperazines (N‐4 = H).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations